YER OSTI SUVLARINI MONITORING QILISHDA AEROKOSMIK TASVIRLARGA RAQAMLI ISHLOV BERISH - Seitnazarov, K.K.; Dosimbetov, A.M.; Turdishov, D.X. (SCIENCE and SOCIETY, 2024)
The article presents an example of Muiynak district of the Republic of Karakalpakstan in order to create a digital model of groundwater based on remote sensing of the Earth, mainly processing aerial photographs. Processing and analysis of remote sensing data from satellites allows you to get most of the information about groundwater.
Keywords: remote sensing; impulse noise; frequency; space image; filtering; image spectrum; algorithm; function; matrix; groundwater